Uji Stabilitas Fisik Sediaan Sirup dari Berbagai Bahan Aktif - Rifka Annisa; Khusnul Khotimah; Nor Latifah (An-Najat, 2025)
This review article discusses the evaluation of physical stability in syrup dosage forms, focusing on three studies that utilized different active ingredients: lime leaf extract, watermelon rind extract, and loratadine. The objective is to assess and compare the outcomes of physical tests such as pH, viscosity, organoleptic properties, and homogeneity under short-term storage conditions. Each study employed an experimental approach by formulating syrup and conducting physical evaluations over a specific period. The results demonstrated that all syrup preparations maintained acceptable physical stability throughout the observation period, with minor variations depending on the formulation and active substance. These findings emphasize the importance of consistent physical stability testing in pharmaceutical product development, especially for liquid dosage forms derived from natural ingredients or commercial drugs. Such testing is crucial to ensure product safety, efficacy, and consumer acceptability during storage and use.